2016
DOI: 10.1097/wco.0000000000000349
|View full text |Cite
|
Sign up to set email alerts
|

How strong is the evidence that Parkinson's disease is a prion disorder?

Abstract: Purpose of review We describe evidence supporting the hypothesis that α-synuclein has a prion-like role in Parkinson’s disease and related α-synucleinopathies, and discuss how this novel thinking impacts the development of diagnostics and disease-modifying therapies. Recent findings Observations that immature dopamine neurons grafted to Parkinson’s disease patients can develop Lewy bodies triggered a surge of interest in the putative prion-like properties of α-synuclein. We recount results from experiments w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 104 publications
1
41
0
Order By: Relevance
“…These results are in line with the findings of some resting-state functional MRI studies, which have demonstrated alterations in resting-state brain activity in the default mode network that consists of the precuneus/posterior cingulate cortex; medial prefrontal cortex; and medial, lateral, and inferior parietal cortex in PD patients with NCPs (Hu et al, 2015;Jia, Li, Li, Liang, & Fu, 2018;Shin et al, 2017;van Eimeren, Monchi, Ballanger, & Strafella, 2009). The fact that PD pathology progresses from the anterior to the posterior parts of the WM (Braak & Del Tredici, 2008;Brundin, Ma, & Kordower, 2016) partially explains the findings of this study.…”
Section: F I G U R Esupporting
confidence: 69%
“…These results are in line with the findings of some resting-state functional MRI studies, which have demonstrated alterations in resting-state brain activity in the default mode network that consists of the precuneus/posterior cingulate cortex; medial prefrontal cortex; and medial, lateral, and inferior parietal cortex in PD patients with NCPs (Hu et al, 2015;Jia, Li, Li, Liang, & Fu, 2018;Shin et al, 2017;van Eimeren, Monchi, Ballanger, & Strafella, 2009). The fact that PD pathology progresses from the anterior to the posterior parts of the WM (Braak & Del Tredici, 2008;Brundin, Ma, & Kordower, 2016) partially explains the findings of this study.…”
Section: F I G U R Esupporting
confidence: 69%
“…). α‐synuclein tends to spread through neurons in a prion‐like manner, and this mechanism of transmission probably underlies the progression of pathological alterations previously described . Furthermore, some data suggest that α‐synuclein aggregation may begin in the autonomic plexi of the gut and spread rostrally and that this could be influenced by the gut microbiome .…”
Section: Pathophysiology Of Pdmentioning
confidence: 86%
“…Studies on experimental models of PD have confirmed the occurrence of trans-synaptic transmission of pathological α -synuclein in vivo [1720]. In light of evidences supporting host-to-graft α -synuclein passage, as well as the ability of the protein to propagate protein misfolding in recipient cells, a “prion-like” hypothesis of PD has been postulated [2129]. Indeed, prions are transmissible misfolded conformers of the prion protein, PrP, which seed further generation of infectious proteins [30].…”
Section: Introductionmentioning
confidence: 99%